One-Time Roll-Forming Technology for High-Strength Steel Profiles with “日” Section - Jicai Liang; Chuandong Chen; Ce Liang; Yi Li; Guangyi Chen; Xiaoming Li; Aicheng Wang (Advances in Materials Science and Engineering)
Roll forming is an important processing method for the production of commercial vehicle anticollision beams, and edge buckling is one of the common defects in roll-forming process. In this paper, the “日” shape section of roll forming is studied, and first the b-shaped section is formed by roll forming, and the internal weld line is automatically welded while forming; then the long side of the b-shaped section is bent into the “U” shape, and the external weld line is welded while forming. The profile is cut off and then bent at both ends to form a commercial vehicle anticollision beam. The ABAQUS finite element software is used to model and analyze the factors affecting the “edge buckling” defect of roll-formed products. This paper uses three factors and three levels of orthogonal simulation experiments to study the problem. The results show that the effect of the factors of flange height, sheet thickness, and forming speed on the formation of edge buckling is in the order of sheet thickness > flange height > forming speed. The edge buckling size of the vertical edge of b-shaped tube decreases with the increase of sheet thickness and increases with the increase of flange height.